Quality function deployment analysis of smartphones - NSB, Akhil; Kumar, Vimal; De, Tanmoy; Klangrit, Suriya (Universitas Negeri Padang, 2022)
To utilize the concept of Quality Function Deployment (QFD) and apply it appropriately to address design decisions concerning the quality of cellular phones, a simplified version of the House of Quality (HoQ) will be built. Real customer requirements (CRs) are easier to collect when QFD is employed because it puts the emphasis on the customer and their demands where it should be. After gathering various users' opinions on different smartphone brands and conducting an online survey with mobile users in Taichung, Taiwan, the study highlights the items preferred by most users, such as long-lasting battery life, high-quality camera, reliability, wide screen, ease of use, and lightweight. This aids businesses in translating CRs into primary Design Requirements (DRs) so that they can create superior goods that align with consumer demands.